Introducing a genetically modified banana in Uganda: Social benefits, costs, and consumer perceptions - Falck-Zepeda, José B.; Kilkuwe, Enoch M.; Wesseler, Justus (International Food Policy Research Institute, 2008)
Banana is a staple crop consumed by Ugandan households. The Uganda National Agricultural Research Organization has implemented conventional and biotechnology programs that seek improving bananas and address the crop's most important pest and disease problems. A major thrust is the development of genetically modified (GM) bananas. The purpose of this paper is to examine potential social welfare impacts of adopting a GM banana in Uganda. The study has three objectives. First, suggest and apply an approach to calculate reversible and irreversible benefits and costs of introducing a GM banana. The study applies a real option approach to estimate, ex ante, the maximum incremental social tolerable irreversible costs (MISTICs) that would justify immediate introduction of the technology. Second, suggest an approach for assessing producer/consumer preferences and willingness to pay (WTP) for introducing a GM banana. Finally, the paper discusses main implications for biosafety decision making for GM crops in Uganda. Results of MISTICs estimation for different scenarios indicate that in delaying the approval of a GM banana, Uganda foregoes potential annual benefits ranging approximately from US$179 million to US$365 million. Average annual MISTICs per household vary between US$34 and US$ 69. Results indicate that only if the average household is willing to give up at least US$38 per year to avoid introduction of a GM banana, should postponing an immediate release be considered. Results imply that although GM bananas promise vast benefits, realization of those benefits depends on consumers' perceptions and attitudes and the willingness to pay for the GM technology.